P3-S1.20 Aetiology of urethral discharge syndrome and its association with sexual practices among males attending STI clinics in India. (10th July 2011) - Kumar, R; Parimi, P; Narayanan, P; Das, A; Gurung, A; Rao, G; Risbud, A
Abstract : Background: Studies to validate the aetiology of urethral discharge (UD) syndrome are limited in India. The objectives of the study were to determine etiological agents of UD syndrome among males attending STI clinics and associated risk factors. Methods: We conducted a cross-sectional study among males presenting with complaints of dysuria and/or urethral discharge at eight government and non-governmental organization STI clinics in four Indian states from 2008 to 2009. A behavioural questionnaire was administered, clinical examination performed and urine was collected to test for Neisseria gonorrhoeae (GC) and Chlamydia trachomatis (CT) by Gen-Probe-APTIMA Combo II. In cases where a urethral discharge was elicited, urethral swabs were collected and tested for Mycoplasma genitalium (MG), Ureaplasma urealyticum (UU) and Trichomonas vaginalis (TV) by using PCR method. Data were analysed using STATA V10. Results: 246 clients diagnosed with UD syndrome as per the national algorithm were enrolled in the study. 29% of the participants had at least one of the infections. The overall prevalence of GC was 14% and CT was 4%. Among the 86 participants from whom urethral swabs were collected, prevalence of MG and UU was 33% and 34% respectively while TV was not detected. In this sub-group of 86 participants, the prevalence of GC and CT was higher at 24% and 7% respectively while 64% individuals had at least one infection. Factors such as younger age (<25 years), illiteracy, paid sex in last 2 weeks and penetrative anal sex in last 3 months were found to be significantly associated with having any infection (see Abstract P3-S1.20 table 1 ). Conclusion: The current practice of diagnosing UD syndrome based on the history of dysuria and/or discharge is leading to over-diagnosis. A detailed sexual history for determining risk factors and demonstration of urethral discharge on clinical examination will help to improve the diagnosis.